2020
DOI: 10.1177/1356336x20915224
|View full text |Cite
|
Sign up to set email alerts
|

‘I always live in a quebrada [favela] and today I am here. So, you can be also here one day’: Exploring pre-service teachers’ perceptions of love for youth from socially vulnerable backgrounds

Abstract: In recent years, socially critical scholars have argued that love, as a moral basis for socio-critical work, should not be colorblind or power blind and that marginalized populations may understand caring within their sociocultural context, creating spaces for youth and teachers to challenge the racism, sexism, class exploitation and linguicism imposed on their communities. While there is advocacy of love in education and physical education, there is little research that aims to explore how pre-service teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“… Thornberg (2008) stated the lack of expertise in value education and explored preventive or proactive approaches, designing and implementing clear rules or standards of behaviors, creating a sense of community among students, and creating a positive school-wide climate and primary response methods for teachers. Luguetti and McDonald (2020) used radical pedagogical approaches to explore pre-service teachers’ perceptions of love for young people from socially disadvantaged backgrounds. Teaching strategies or approaches have always been a critical area of research in teaching and learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Thornberg (2008) stated the lack of expertise in value education and explored preventive or proactive approaches, designing and implementing clear rules or standards of behaviors, creating a sense of community among students, and creating a positive school-wide climate and primary response methods for teachers. Luguetti and McDonald (2020) used radical pedagogical approaches to explore pre-service teachers’ perceptions of love for young people from socially disadvantaged backgrounds. Teaching strategies or approaches have always been a critical area of research in teaching and learning.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it can fill gaps and contribute to the construction of curricula that can make curricular goals a reality in the classroom ( Roux and Dasoo, 2020 ). For students, it can bring changes in behaviors and greater interest in participating in society ( Luguetti and McDonald, 2020 ). It can improve existing teacher education, promote teachers’ professional development ( Thornberg et al, 2013 ), promote patriotic education, and give students a global perspective ( Wong et al, 2017 ; O’Flaherty and McCormack, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Having care-experienced volunteers working with young people might help in the process of developing mutual trust and respect and consequently the translation in the concept of radical love. In a similar finding, Luguetti and McDonald (2020) studied pre-service teachers from socially vulnerable backgrounds who were working with young people from the same backgrounds and found that they embodied experiences of oppression, which created a space for them to see themselves in the young people, to reconnect with their own identity, and develop empathy. They concluded that these experiences helped them give back to their community, creating more socially just communities.…”
Section: Mutual Trust and Respect Radical Love And The Context Of Footballmentioning
confidence: 91%
“…There is an absence of studies in the field of sport for development that apply CRP as an analytical lens. However, culturally relevant pedagogies have been illuminated in previous studies that discuss critical pedagogy to co-create social change with young people (e.g., Luguetti & McDonald, 2020;Nols et al, 2018;Spaaij et al, 2016;Spaaij & Jeanes, 2013). These studies discuss a culturally responsive pedagogy based on dialogue and problem posing.…”
Section: Applications Of Crp In Physical Education and Sport Pedagogymentioning
confidence: 99%
“…Community-driven sport programs potentially offer an alternative to the deficit model which positions young people as 'problems' to be fixed, overlooks their agency and/or associates refugee-background young people's difference and marginality with deficit and lack (Keddie, 2012;Thorpe, 2020). By centring young people through culturally responsive pedagogies, programs can create spaces to better address their needs and aspirations, focused on generating changes within local communities through empowering both coaches and young people and developing a critical awareness of their relationship with the world (Luguetti & McDonald, 2020). In this approach, programs are co-designed specific to the local context and the conditions in which young people live, amplifying their voices and respecting their knowledge as legitimate (Thorpe, 2020).…”
Section: Introductionmentioning
confidence: 99%